A chemoenzymatically synthesized cholesterol-g-poly(amine-co-ester)-mediated p53 gene delivery for achieving antitumor efficacy in prostate cancer - Dong M (Dove Medical Press, 2019)
Mengmeng Dong,1,2,* Jiawen Chen,2,* Jiayuan Zhang,2 Xiao Liang,2 Jiebing Yang,2 Dan Li,1 Quanshun Li2 1Department of Cancer Center, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 2Key Laboratory for Molecular Enzymology and Engineering of Ministry of Education, School of Life Sciences, Jilin University, Changchun 130012, People’s Republic of China *These authors contributed equally to this work Background: An amphiphilic cationic copolymer cholesterol-g-poly(amine-co-ester), namely Chol-g-PMSC-PPDL synthesized in a chemoenzymatic route has been utilized as a carrier for p53 gene delivery to check its antitumor efficacy, using human prostate cancer cell line PC-3 (p53 null) as a model. Materials and methods: The transfection efficiency was measured by quantitative PCR and Western blotting assay. The anti-proliferative effect was detected using MTT method, colony formation assay and Live/Dead staining. The anti-migration effect was evaluated through wound healing and Transwell migration assays. Results: The transfection efficiency assay indicated that the carrier-mediated p53 gene transfection could dramatically enhance the intracellular p53 expression level. Through p53 gene delivery, obvious anti-proliferative effect could be detected which was elucidated to be associated with the simultaneous activation of mitochondrial-dependent apoptosis pathway and cell cycle arrest at G1 phase. Meanwhile, the anti-migration effect could be obtained after p53 gene transfection. Conclusion: Chol-g-PMSC-PPDL-mediated p53 gene transfection could potentially be employed as a promising strategy for achieving effective anti-tumor response. Keywords: cholesterol-g-poly(amine-co-ester), p53 gene delivery, gene therapy, anti-proliferation effect, anti-migration effect